2018
DOI: 10.1111/pde.13426
|View full text |Cite
|
Sign up to set email alerts
|

Skin lesions serve as clues to relapse of pediatric blastic plasmacytoid dendritic cell neoplasm

Abstract: A 10-year-old girl with a history of blastic plasmacytoid dendritic cell neoplasm, a rare malignancy in children, presented with recurrent skin eruptions beginning while on maintenance chemotherapy, including mildly pruritic skin-colored plaques, tender indurated nodules, and violaceous bound-down plaques. This case highlights an unusual presentation of relapsed blastic plasmacytoid dendritic cell neoplasm on chemotherapy, with skin lesions providing important clues to the progression of systemic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Cutaneous disease can also indicate relapse or progression. Dreyer et al reported a 10‐year‐old girl with initial extracutaneous BPDCN who developed diffuse indurated nodules and violaceous bound‐down plaques while on maintenance chemotherapy 7 . Sun et al reported a 15‐year‐old with BPDCN who, after initially presenting with periorbital ecchymoses, developed new breast and periorbital lesions along with a chest wall rash after relapse 8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutaneous disease can also indicate relapse or progression. Dreyer et al reported a 10‐year‐old girl with initial extracutaneous BPDCN who developed diffuse indurated nodules and violaceous bound‐down plaques while on maintenance chemotherapy 7 . Sun et al reported a 15‐year‐old with BPDCN who, after initially presenting with periorbital ecchymoses, developed new breast and periorbital lesions along with a chest wall rash after relapse 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, the CD123 inhibitor tagraxofusp (SL401) was trialed in three pediatric BPDCN patients; two responded quickly to therapy and the other did not respond. None of the patients suffered adverse effects 7 . In 2018, the FDA approved tagraxofusp for treatment of BPDCN in patients 2 years and older, although with a black box warning for possible capillary leak syndrome (noted in 19% of patients) 12 .…”
Section: Discussionmentioning
confidence: 99%
“…1,5 Infrequently, patients do not have skin lesions at the time of diagnosis, but they can appear later in the course of disease, or serve as clues to relapse. 6 Interestingly, Kim et al reported that 100% of pediatric patients without cutaneous lesions at initial presentation were shown to be alive and disease-free at follow-up, probably related to the treatment administered (ALL protocols) or limited-stage disease. 3 About 80% of pediatric cases have extracutaneous organ involvement at the time of initial staging.…”
Section: Discussionmentioning
confidence: 99%